Lice outbreak in buffaloes: Evidence of Anaplasma marginale transmission by sucking lice Haematopinus tuberculatus - Da Silva A.S.* (2013)
Lice infestations are commonly seen in buffaloes, causing damage directly to the animal, i.e., itching, skin lesions, and anemia. In addition, these insects can also be vectors for infectious diseases. The present study describes an outbreak of lice in buffaloes as well as evidence for Haematopinus tuberculatus acting as a vector of anaplasmosis. Lice and blood were collected from 4 young buffaloes (2- to 4-mo-old) and a molecular analysis for the presence of Anaplasma marginale was conducted. DNA of A. marginale was detected in the blood of all 4 animals. Twelve lice were collected and separated in 4 groups, with 3 insects each, to comprise a pool of samples. After DNA extraction and molecular analysis, a positive PCR for A. marginale was found in all pooled samples. These results identify sucking lice as potential vectors of anaplasmosis. However, additional studies are necessary to fully evaluate the vector potential of H. tuberculatus for A. maginale transmission. © 2013 American Society of Parasitologists.